A Comparative Analysis of Lynne Sedgmore’s Spiritual Leadership and its Potential Usefulness in the Irish Post-Primary Setting - Considine, Sarah (Marino Institute of Education, 2020)
The past two decades have seen a heightened expression of interest in the field of spiritual leadership, and a growing body of literature and research has proven that spiritual leadership can yield positive consequences for schools and organisations. This thesis investigates and explores Lynne Sedgmore’s spiritual leadership, and identifies the positive implications of spiritual leadership. Insights into Sedgmore’s career as a spiritual leader in the Further Education sector have been presented, with her legacy as Chief Executive at the Centre for Excellence in Leadership most thoroughly examined. Her work with this organisation saw her cultivate an energetic, creative, and motivated working community, which led its corporate success. Louis W. Fry, Yochanan Altman, and Parker J. Palmer have written extensively in the area of spirituality and leadership, and their insights have also been presented. Their work in this field and their understanding of the concept affirms the positive nature of Sedgmore’s spiritual leadership. This can be seen through comparisons drawn between her and each of these academics and practitioners. The findings of the analysis revealed the beneficial implications of spiritual leadership in the Irish post-primary context. Practical suggestions and recommendations have been made to inspire principals in their role as a spiritual leader.